1986
DOI: 10.1099/0022-1317-67-7-1373
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of p28 Adult T-Cell Leukaemia-associated Antigen

Abstract: SUMMARYThe 28 000 mol. wt. polypeptide (p28) of adult T-cell leukaemia-associated antigen encoded by the 24S defective human T-cell leukaemia virus (HTLV-I) is associated with protein kinase activity. We have determined the nucleotide sequence of this defective HTLV-I provirus and found that it contains a portion of the gag gene (p19 and part of p24), the pX region, and two long terminal repeats, one at each end. The predicted p28 gag-pX fused protein consists of 190 amino acids and its mol. wt. was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This difference in the predicted and observed masses may be attributable to the high content of acidic and proline residues comprising the PRLBP (21%). Previous studies have reported this same discrepancy because of the retarded mobility of a variety of proteins based on proline and acidic residue content (23)(24)(25). To confirm the identity of the PRLBP with the PRLR ECD, the immunoprecipitated PRLBP was subjected to limited proteolysis and SDS-polyacrylamide gel electrophoresis analysis alongside similarly digested rhPRLR ECD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the predicted and observed masses may be attributable to the high content of acidic and proline residues comprising the PRLBP (21%). Previous studies have reported this same discrepancy because of the retarded mobility of a variety of proteins based on proline and acidic residue content (23)(24)(25). To confirm the identity of the PRLBP with the PRLR ECD, the immunoprecipitated PRLBP was subjected to limited proteolysis and SDS-polyacrylamide gel electrophoresis analysis alongside similarly digested rhPRLR ECD (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MT-2 cells contain one complete provirus and seven defective proviral sequences (27). A 3.4-kb RNA transcript of the defective proviruses expresses a myristylated truncated Gag protein that is composed of MA, a truncated CA, a short pX region, and two long terminal repeats (28). The 3.4-kb RNA transcript and the truncated Gag proteins have previously been found packaged into virus particles produced from MT-2 cells (20).…”
mentioning
confidence: 99%
“…In this cell line, besides a complete provirus, seven defective proviruses were detected by Southern hybridization, and four of them were found to be identical with a large internal deletion resulting in the 5Ј portion of the gag gene being linked to a pX region (15,16). These proviruses contained an open reading frame (ORF) coding for a chimeric protein (p28) composed of Gag (MA [matrix] and truncated CA [capsid]) and a short pX fragment (12). RNA transcripts for MT-2 cell defective provirus are packaged in virions and can be translated into a p28 chimeric protein (25), and they establish new provirus in culture (1).…”
mentioning
confidence: 99%